ANALISIS PENERAPAN SOCIAL MEDIA MARKETING INSTAGRAM PADA HOTEL HORISON PALMA PANGANDARAN MENGGUNAKAN FRAMEWORK DRAGONS - Nur Iman Firmansyah; Arianis Chan; Raden Ratna Meisa Dai (JURNAL LENTERA BISNIS, 2024)
Hotel Horison Palma Pangandaran is a company engaged in the hotel industry. This research aims to obtain information and a real picture of how to implement  the Instagram social media marketing strategy at the Horison Palma Pangandaran Hotel. The research method used is qualitative descriptive which explains descriptively how to implement  the Instagram social media marketing strategy  carried out by Hotel Horison Palma Pangandaran. The data collection technique of this study is through interviews with 6 informants, documentation and literature studies, source triangulation, and using the DRAGONS framework analysis. The results of this study show that the company in implementing the dimensions  of content creation, content sharing, and community building has been running well. Meanwhile,  the connecting dimension  still experiences several obstacles that can be repaired and maximized by the Horison Palma Pangandaran Hotel.